Gender Equality in Narratives and Illustrations Contained in Integrated Thematic Books for Class I Students in the 2013 Curriculum in Primary Schools - Ismail; Rahman, Nurhayati; Adi Armin, Mardi (Mutiara Intelektual Indonesia Press, 2023)
This research aims to describe gender equality in the narratives and illustrations contained in the integrated thematic books for class I students in the 2013 curriculum in elementary schools. This study used descriptive qualitative method. The data collection methods used were literature study, observation, documentation and note taking. In data processing, we use a qualitative approach using Nature theory and semantics. Based on the results of the research and discussions that have been carried out, it can be concluded that the substance of the book's content contains gender inequality. Gender inequality is reflected through illustrative images and story text which fall into three categories, namely (1) Gender inequality in trait values, (2) Gender inequality in work roles, and (3) Gender inequality in hobbies. Each category depicts a woman who is feminine, weak, irrational, emotional and plays a lot of roles in domestic matters. Women are not in an equal position with men who have a masculine attitude and are able to play a role in public matters. Gender bias can influence student teaching and learning activities, such as: using appropriate methods that involve all students, classroom management such as assigning seats to the class teacher, dividing them randomly without looking at the gender and achievement of the students and changing them once a month so that students don't feel bored. and student interactions, especially those that occur outside the classroom, involve interactions between students. Male students usually play with members of the same gender, while female students also play with female friends to make it easier for students to choose the games they play